Nghiên cứu sự tạo liên hợp ion của vonfram (VI) với thuốc thử metyl tím 2B (M2B) trong môi trường nước-axeton bằng phương pháp chiết-trắc quang và khả năng ứng dụng vào phân tích - Thụ, Lâm Ngọc; Thiềm, Lâm Ngọc; Tuấn, Vi Anh (Vietnam Journal of Chemistry, 2014)
The interaction of tungsten(VI) with M2B has been investigated in acetone-aqueous medium. The complex has been examined by solvent extraction-spectrophotometry method. In optimum conditions (pH 3; 30% (v/v) acetone) the ion-association complex of tungsten(VI) with M2B was formed with ratio 2:1, and it was extracted quantitatively one time with 5 mL toluene. In organic phase, the complex has maximum absorption at 591 nm, and stable at least 2 hours after extraction. The complex is formed completely when concentration of M2B is three times of that of tungsten(VI). Concentration of molybdenum(VI) up to 200 times of that of tungsten(VI) did not interfere. The results have shown that absorbance of the complex obeys Beer’s law in a rather large range. Therefore, the complex could be used for micro determination of tungsten(VI) in steel.